Hypoglycemia as a sign of paraneoplastic syndrome in a patient with pleural fibroma - Sagova, Ivana; Kantárová, Daniela; Stancik, Matey; Klimentová, Adriana; Sadloňová, Jurina; Mokáň, Marian (European Journal of Oncology and Environmental Health, 2015)
Paraneoplastic syndrome has a wide range of symptoms and fasting hypoglycemia is one of its possible clinical manifestations. It is mostly caused by insulinomas and non-islet cell tumors (large mesenchymal tumors account for more than a half of all neoplasms associated with hypoglycemia). Clinical features may vary and typical laboratory features of paraneoplastic hypoglycemia includes low level of fasting glucose and C-peptide, low insulin growth factor 1 (IGF1) and elevated level of “big” insulin growth factor 2 (IGF2). The increased IGF2 : IGF1 ratio is considered to be pathognomic for this diagnosis. Although paraneoplastic hypoglycemia is mostly present in patients with the already diagnosed malignancy, it is necessary to consider this opportunity in patients having unclear and inexplicable hypoglycemia. The adequate treatment can significantly reduce the symptoms and improve the quality of life.